(untitled) (Revista Contexto & Educação, 2024)
This article explores the Citizen School of Porto Alegre, a progressive educational project implemented in the 90s as a response to neoliberal policies. The overall objective is to analyze the concepts of curriculum and learning assessment from the perspective of Paulo Freire, focusing on social transformation and the democratization of education. The methodology involves a documentary and bibliographic review, highlighting community participation and democratic management as pillars of the project. The results indicate that the curriculum of the Citizen School is dynamic, integrating cultural and local knowledge, and the assessment is procedural and continuous, focused on student development. The reflections point to transformative impact of an educational model that promotes active citizenship and critical formation. In conclusion, despite structural and political challenges, the Citizen School offers a viable reference for inclusive and transformative education, reaffirming education as a field of resistance and social emancipation.